Loss of extrasynaptic inhibitory glycine receptors in the hippocampus of an AD mouse model is restored by treatment with artesunate - Kuhse, Jochen; Groeneweg, Femke; Kins, Stefan; Gorgas, Karin; Nawrotzki, Ralph; Kirsch, Joachim; Kiss, Eva (International journal of molecular sciences, 2023)
Alzheimer’s disease (AD) is characterized by synaptic failure and neuronal loss. Recently, we demonstrated that artemisinins restored the levels of key proteins of inhibitory GABAergic synapses in the hippocampus of APP/PS1 mice, a model of cerebral amyloidosis. In the present study, we analyzed the protein levels and subcellular localization of α2 and α3 subunits of GlyRs, indicated as the most abundant receptor subtypes in the mature hippocampus, in early and late stages of AD pathogenesis, and upon treatment with two different doses of artesunate (ARS). Immunofluorescence microscopy and Western blot analysis demonstrated that the protein levels of both α2 and α3 GlyRs are considerably reduced in the CA1 and the dentate gyrus of 12-month-old APP/PS1 mice when compared to WT mice. Notably, treatment with low-dose ARS affected GlyR expression in a subunit-specific way; the protein levels of α3 GlyR subunits were rescued to about WT levels, whereas that of α2 GlyRs were not affected significantly. Moreover, double labeling with a presynaptic marker indicated that the changes in GlyR α3 expression levels primarily involve extracellular GlyRs. Correspondingly, low concentrations of artesunate (≤1 µM) also increased the extrasynaptic GlyR cluster density in hAPPswe-transfected primary hippocampal neurons, whereas the number of GlyR clusters overlapping presynaptic VIAAT immunoreactivities remained unchanged. Thus, here we provide evidence that the protein levels and subcellular localization of α2 and α3 subunits of GlyRs show regional and temporal alterations in the hippocampus of APP/PS1 mice that can be modulated by the application of artesunate.